Practicing Task-Specific Instability Challenge in Performance and Acquisition of a Complex Motor Skill - Fariba Hasanbarani; Mehdi Shahbazi; Shahzad Tahmasebi-Broujeni; Mohammadali Sanjari; Jamal Fazel-Kalkhoran (Vesnu Publications, 2017)
Introduction: Motor skill acquisition studies have shown that the performance of a motor task will be smoother after practice; however, the type of practice is very important. Thus, the aim of this study was to investigate the effect of practice with task-specific instability on performance and acquisition of a throwing skill. Materials and Methods: This quasi-experimental study was conducted on 16 semi-skilled subjects under 2 practice conditions, with and without availability of visual feedback. Each practice stage involved 3 blocks of 10 trials. The subjects' throwing skill was evaluated in pretest and posttests, before and after the practicing stages. Two repeated measures ANOVA and paired t-test were used to examine the differences between subjects in practicing and test stages at a significance level of 0.05. Results: No significant difference were observed between practice blocks in the two stages of practice; however, there were significant differences between pretest and posttest with blocks in the second stage (P = 0.001). Moreover, no significant differences were observed between the posttests of the two practice stages. Conclusion: Task-specific instability with blocking of visual feedback not only induces the acquisition of complex motor skills, but also prepares the individual for confronting unstable conditions. It is suggested that coaches and therapists train athletics and patients for performing complex skills under unstable conditions to better prepare them for confronting these conditions.